Pedagogical-Psychological, Pragmatic Features of Improving the Tasks that Develop Verbal Competence - Mekhriban Uteulieva Ibraimovna (Research Parks Publishing LLC, 2021)
The article presents a scientific approach to topics including mother tongue instruction, children's speech development, new methods of speech development, incentive to enhance speaking abilities, pragmatism - bringing education closer to life, and many scholars' scientific perspectives.